Lipid glycosylation: a primer for histochemists and cell biologists - Kopitz, Jürgen (Histochemistry and cell biology, 2017)
Glycolipids are glycoconjugates that are predominantly found on the extracellular surface of cells ranging from bacteria to men. In bacteria and plants, glycoglycerolipids represent the main glycolipid species. Ceramides as carrier for glycans, termed glycosphingolipids (GSLs), are characteristic for vertebrates and insects. The glycan part is involved in a variety of biological activities including cell adhesion and initiation of signaling. Most of these functions rest on two basic principles: (1) GSLs spontaneously contribute to organize lipid rafts in biological membranes, thereby forming functional complexes (‘glycosynapses’) with receptor proteins and ion channels and (2) their glycans are bound by receptors like galectins (protein-glycan recognition) or cognate glycans (glycan-glycan recognition). This interaction modulates cell adhesion, differentiation and growth processes. Besides their contribution to normal cell behavior, GSL expression patterns also influence disease processes by inducing cellular malfunctions when aberrant, as highlighted by inherited disorders of GSL metabolism like sphingolipidoses. Altered GSL patterns are also associated with common neurological diseases, autoimmune diseases and cancer. With respect to infections, various GSL-presented glycans are attachment sites for bacteria and viruses as well as primary targets for bacterial toxins. This review provides an introduction to GSL structures, their nomenclature and metabolism. Building on this, normal and pathological functions of GSL will be surveyed.
First online: 20 December 2016
Gesehen am 14.11.2018